ROLE OF THE INTERNATIONAL ECONOMIC ORGANIZATIONS IN THE DECISION OF PROBLEM OF DEOFSHORIZATION IN THE FOREIGN COUNTRIES - Y. Grigoryeva (Вестник университета)
In recent years problems of deofshorization were staticized in view of need of ensuring steady participation of the countries for international capital movement. In the article approaches of the international organizations to regulation of anti-ofshore activities at the present stage are generalized.